Transfusion challenges and management strategies in Bombay blood group pregnancies: a case series - Poobalan, K.; Krishnamoorthy, R.; Ashwin, A.; Rathan, R. Niranj; Kumar, M. Sampat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
The Bombay blood group (Oh phenotype) is a rare blood type characterized by the absence of the H antigen, rendering standard O group transfusions incompatible. Its rarity presents unique challenges in obstetric care, where transfusion preparedness is critical. We describe the clinical course, transfusion planning, and perinatal outcomes in three pregnant women with the Bombay blood group. Three antenatal patients with confirmed Bombay phenotype (O Rh[D] positive) were managed at our tertiary care center between 2023 and 2025. All were primigravidae or with precious pregnancies, and two had moderate anemia corrected with intravenous iron. Bombay-compatible blood units were arranged in advance through a rare donor registry. Case 1 had spontaneous vaginal delivery and required a single unit transfusion post-delivery, complicated by a mild allergic reaction. Case 2, with IVF conception and severe preeclampsia, underwent emergency caesarean section complicated by atonic postpartum hemorrhage (PPH) managed medically and with a Bakri balloon. One unit of Bombay blood was transfused postoperatively. Case 3 underwent elective caesarean delivery without transfusion. Key management strategies included early blood group identification, proactive donor coordination, and prioritization of non-transfusion approaches for anemia correction. Multidisciplinary collaboration with transfusion services ensured timely access to compatible blood and safe delivery. Pregnancy in Bombay blood group women requires individualized planning and a multidisciplinary approach. Early diagnosis, rare donor registry utilization, and non-transfusion anemia correction play pivotal roles in optimizing maternal and neonatal outcomes.